DEVELOPMENT OF YOUTH ATTENTION - Tojiddinova Laylokhan Shokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Through the article, you will learn about the place and importance of attention in a person’s life. In students, you will have information about the peculiarities of attention, the strength and stability of attention and its scale.